Sentiment analysis and information diffusion in social media: a study on Malaysia’s university - Tan, Sze Mei (2020)
As for now, social media is being part of an individual life. Even academic institution tends to shift their marketing channel to social media. Social media usage is increasing tremendously and there provide opportunities to investigate how information in social media diffuse among the users as online networking sites can mirror the structure of disconnected human culture. As social media motivates two-way communication, a snippet of data can be traded or diffused between people in interpersonal organizations. From this dissemination procedure, bunches of inactive data can be mined. It can be utilized to study the relationship between information diffusion process and sentiment of posts. Consequently, data is collected from Facebook higher educational institution page in Malaysia and being analysed. The motivation behind this paper is to help on branding higher education in Malaysia. A conceptual framework which is inspired by the research of de Vries et al. (2012) is proposed to investigate the correlation between 6 influential factors and the number of likes, comments and shares. Among the 6 factors, there is 2 factors which are newly added in this research: sentiment of the post and use of hashtag. The result shown that use of hashtag is positive correlated with information diffusion while positive posts have shown a weaker positive relationship with information diffusion. The negative posts have shown a weak negative relationship with information diffusion. Among the 6 factors, entertaining factor has the highest coefficient for the number of likes and comments while information content and use of hashtag have the highest coefficient for number of shares.